Changes of Morphology, Chemical Compositions, and the Biosynthesis Regulations of Cuticle in Response to Chilling Injury of Banana Fruit During Storage - Huang, Hua; Wang, Ling; Qiu, Diyang; Zhang, Nan; Bi, Fangcheng (Frontiers in Plant Science, 2021)
The plant cuticle covers almost all the outermost surface of aerial plant organs, which plays primary function in limiting water loss and responding to the environmental interactions. Banana fruit is sensitive to thermal changes with chilling injury and green ripening below 13 oC and over 25 oC, respectively. Herein the changes of surface morphology, chemical compositions of cuticle as well as the relative expression of cuticle biosynthesis genes in banana fruit under low temperature storage were comprehensively investigated. Banana fruit exhibited chilling injury rapidly with browned peel appearance stored at 4 oC for 6 d. The surface altered apparently from the clear plateau with micro-crystals to smooth appearance. The overall coverage of main cuticle pattern of waxes and cutin monomers increased about 22 % vand 35 %, respectively, in browned banana as compared to normal ones stored under low temperature at 6 d. Fatty acids (C16 and C18) and ω-OH, midchain-epoxy fatty acids dominated cutin monomers, while the monomers of fatty acids, and the low abundant ω, midchain-diOH fatty acids, and 2-hydroxy fatty acids increased remarkably under low temperature. The cuticular waxes were dominated by fatty acids (> C19), n-alkanes, and triterpenoids; and the fatty acids and aldehydes were shifted to increase accompanied by the chilling injury. Furthermore, RNA-seq highlighted 111 cuticle-related genes involved in fatty acid elongation, biosynthesis of very-long-chain aliphatics, triterpenoids, and cutin monomers, and lipid-transfer proteins were significantly differential regulated by chilling temperature. The cuticle covering on fruit surface was also involved to respond to the chilling injury of banana fruit after harvest. These findings provide useful insights to link the cuticle on basis of morphology, chemical composition changes and their biosynthesis regulations in response to the thermal stress of fruit during storage.